The Role of Human Resource Management in Improving Hospital Service Quality to Support Accreditation at Grandmed Hospital Lubuk Pakam - okto, Okto Hebron Purba; Anggi Kurnia Ningsih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Human resource management (HRM) is a key factor in improving hospital service quality and achieving accreditation. This study aims to analyze the role of HRM in supporting the achievement of accreditation standards at Grandmed Hospital Lubuk Pakam. The research method employed was literature review and descriptive analysis of hospital documents, including HR policies, training programs, performance evaluations, and quality culture. The findings show that HRM plays a crucial role through workforce planning based on service needs, competency-based recruitment and selection, continuous training on patient safety, performance appraisal using quality indicators, motivation and staff retention strategies, as well as strengthening quality and patient safety culture. The implementation of these six aspects has been proven to enhance hospital readiness in meeting accreditation standards while positively impacting service quality and patient satisfaction. In conclusion, optimizing HRM at Grandmed Hospital is an essential strategy to achieve accreditation and ensure safe, effective, and sustainable healthcare services.